Implementation of an HRIS (Human Resource Information System) as a Digitalization Strategy to Improve Human Resource Efficiency: A Case Study at PT. Tenggara Multi Media Gemilang - Setiowati, Reni Diah; Santoso, Robi; Pratama, Agung (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the implementation of the Human Resource Information System (HRIS) as a digitalization strategy in improving the efficiency of human resources at PT. Tenggara Multi Media Gemilang. This case study was conducted with a qualitative approach through observation, interviews, and document analysis to understand the conditions of HR management before and after the implementation of HRIS. The results of the study test whether the implementation of HRIS is able to automate human resource (HR) administrative processes such as employee data management, attendance, payroll, and reporting, thereby reducing manual workload, minimizing data errors, and accelerating the decision-making process at the managerial level. In addition, centralized and real-time integration of human resource data through the Human Resource Information System (HRIS) can increase transparency, information accuracy, and coordination between divisions at PT. Tenggara Multi Media Gemilang. Although there are still challenges in the form of user adaptation and the need to improve human resource (HR) competencies. Thus, the implementation of HRIS at PT. Tenggara Multi Media Gemilang is expected to help its effectiveness as a digitalization strategy that supports increasing efficiency, productivity, and quality of human resource (HR) management.